Cognitive radio auto-adaptive sensing algorithm based on POMDP - Rui-chen XU; Ting JIANG (Tongxin xuebao)
In order to design an appropriate spectrum sensing mechanism in millisecond spectrum hole environment,the optimal data transmission time of secondary users was derived to maximize the data throughput.Furthermore,in order to exploit the millisecond spectrum holes,an auto-adaptive spectrum sensing algorithm based on POMDP (partially observ-able Markov decision process) was proposed.This algorithm executes spectrum sensing or data transmission action in the current decision epoch based on the belief vector and the observation result in the last decision epoch.Simulation results show that the proposed algorithm can constrain the collision probability between primary users and secondary users,and improve systemic spectrum utilization at the same time.